Cost Analysis of Construction Safety Management Systems: Compliance Assessment with Indonesian Safety Regulations - Rahman, Ari Syaiful Syaiful; Faisal Ashar; Fitra Rifwan; Nevy Sandra (CIVED, 2025)
The Indonesian construction sector plays a vital role in national economic development, yet it continues to face significant occupational safety challenges. This study assesses the implementation of Construction Safety Management Systems by national safety regulations, with a focus on compliance within the XYZ construction project. Using a mixed-methods approach, the research combines quantitative budget analysis with qualitative field observations and interviews with safety officers. Findings indicate that while safety measures were implemented, budget allocations remained insufficient to meet regulatory requirements. Critical components, such as safety training and preventive risk control measures, were notably underfunded, reflecting gaps between policy mandates and their practical execution. The study highlights systemic challenges in safety budget planning, including inconsistent incorporation of regulatory standards and disproportionate allocation across safety components. These findings contribute to broader discussions on construction safety governance in emerging economies, emphasizing the need for improved compliance mechanisms and accountability frameworks. Practical recommendations include the adoption of risk-based budgeting approaches and enhanced oversight to ensure adequate safety investments. The research provides valuable insights for policymakers and industry stakeholders seeking to strengthen safety management practices in public construction projects.